MENINGKATKAN KESADARAN PENGASUHAN ANAK DI ERA DIGITAL MELALUI CERAMAH BERBASIS MULTIMEDIA - Eka Damayanti; Arifuddin Ahmad; Nurhasanah Nurhasanah (Raheema, 2021)
The study aims to determine the enhancement of parenting awareness in the digital era through lectures based on multimedia. This study was the result of community service by giving lectures based on multimedia. The population of this study was 20 mothers of Majelis Taklim, a women Islamic forum of Nuha district and there were 18 mothers selected randomly as the samples. Data was collected by using instruments of psychology scale through Google forms and analyzed descriptively. The result showed the increased of parenting awareness. The score of understanding of the child's development was 20 and so do the understanding of the gadget’s impact on child development. The score on raising awareness of Islamic concepts in parenting was 17 and the score of the awareness of parents’ responsibilities in preventing the impact of gadgets was 18. The score of clarity measures in preventing the impact of gadgets was 25 and readiness of implementing prevents the impact of gadgets’ score was 19.